Advances in Cryptology — EUROCRYPT ’91
DOI: 10.1007/3-540-46416-6_4
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Low-Density Subset Sum Algorithm

Abstract: Abstract. The general subset sum problem is NP-complete. However, there are two algorithms, one due to Brickell and the other to Lagarias and Odlyzko, which in polynomial time solve almost all subset sum problems of sufficiently low density. Both methods rely on basis reduction algorithms to find short non-zero vectors in special lattices. The Lagarias-Odlyzko algorithm would solve almost all subset sum problems of density < 0.6463... in polynomial time if it could invoke a polynomial-time algorithm for findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 16 publications
0
65
0
Order By: Relevance
“…Their attack does not incorporate the weakness on the trapdoor itself, rather than only using the fact that the knapsack problems produced are generally weaker that a random one. This result was subsequently improved in [25,24,66,58]. Nevertheless, some improvements of knapsack cryptosystems were also proposed (e.g.…”
Section: Knapsack Cryptosystemsmentioning
confidence: 99%
“…Their attack does not incorporate the weakness on the trapdoor itself, rather than only using the fact that the knapsack problems produced are generally weaker that a random one. This result was subsequently improved in [25,24,66,58]. Nevertheless, some improvements of knapsack cryptosystems were also proposed (e.g.…”
Section: Knapsack Cryptosystemsmentioning
confidence: 99%
“…We have chosen knapsack lattices [19,9,8,28,10] and random lattices (as defined by Goldstein and Mayer [12,27]) as examples for sparse lattice bases. Unimodular lattice bases serve as representatives for dense lattice bases Previous experiments [37,2] showed that unimodular lattice bases are more difficult to reduce than, e.g., knapsack lattices given the same dimension and maximum length of the basis entries.…”
Section: Lattice Basesmentioning
confidence: 99%
“…when the function is used in expansion mode). According to [9], the best known provable lattice attack of this type [4] succeeds with high probability over a random choice of a[1], . .…”
Section: Definition 4 (Subset Sum Problemmentioning
confidence: 99%
“…and try to use the method of [4] to find a solution involving only those integers (i.e. set the n − n remaining weights to zero).…”
Section: Definition 4 (Subset Sum Problemmentioning
confidence: 99%